Could Hong Kong be developed as a romantic destination of tourism? - Jim, Chun-hing (2006)
Contrary on the common belief of Hong Kong as a tourist destination of shopping paradise, Hong Kong does have the romantic elements in which there is the potential for Hong Kong to be repositioned in the international tourism market to be a romantic destination for attracting newlyweds to celebrate their honeymoons here and for married couples for celebrating their marriage anniversary.